2010
DOI: 10.1002/uog.7542
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical vein anomaly in fetuses with Down syndrome

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…According to Berg et al, 8 it is suggested that in the presence of cardiac malformations, complex nonchromosomal malformation syndromes in combination with an absent ductus venosus are significantly associated with intrauterine or postnatal death independent of the venous drainage site. The potential association of an aberrant right subclavian artery with chromosomal anomalies (particularly Down syndrome) and nonchromosomal defects (congenital heart disease) has been well established 9 , 10 . The observed subclavian vessel rearrangement in our case was in line with previous reports of an aberrant right subclavian artery accompanying cardiac defects as part of underlying genetic disorders.…”
supporting
confidence: 91%
“…According to Berg et al, 8 it is suggested that in the presence of cardiac malformations, complex nonchromosomal malformation syndromes in combination with an absent ductus venosus are significantly associated with intrauterine or postnatal death independent of the venous drainage site. The potential association of an aberrant right subclavian artery with chromosomal anomalies (particularly Down syndrome) and nonchromosomal defects (congenital heart disease) has been well established 9 , 10 . The observed subclavian vessel rearrangement in our case was in line with previous reports of an aberrant right subclavian artery accompanying cardiac defects as part of underlying genetic disorders.…”
supporting
confidence: 91%
“…Achiron et al 40 have found that in 11% the UV was connected to the hepatic portion of the inferior vena cava (IVC) at a position lower than its usual site while only 0.12% fetuses with normal karyotype demonstrated similar anomalous insertion of the UV into the IVC, making the OR for abnormal umbilicoportal venous system in fetuses with DS compared with the normal population of 107.4. Our case had also the same UV anomaly.…”
Section: Trisomy 21-case Reports and Literature Reviewmentioning
confidence: 96%
“…Abnormal drainage of the fetal umbilical vein (UV) with absence of the ductus venosus (DV) is a rare condition with a prevalence of 1 per 2500 fetuses 1 , 2 . Previous reports described an association with additional congenital malformations.…”
mentioning
confidence: 99%
“…Other studies reported drainage of the UV directly into the IVC in fetuses with hydrops fetalis and cardiovascular malformations 4 – 7 . Achiron et al 2 reported an increased risk of abnormal connection of the UV to the hepatic portion of the IVC at a position lower than its usual site in fetuses with Down syndrome, and Staboulidou et al 8 reported an association with aneuploidies.…”
mentioning
confidence: 99%
See 1 more Smart Citation